(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
A series of proctor compaction and CBR tests (un-soaked and soaked) are carried out on clayey soil, mixed with various stabilizers (cement and Recron fiber) in different percentages. Cement is mixed at the rate of 3%, 5% and 7% by weight of dry soil, whereas Recron fiber (6mm) are mixed at the rate of 0.3%, 0.5%, 1%, 2%, and 3% by weight of dry soil. For better performance a combination of different stabilizers in clayey soil (considering best dose of individual) are also evaluate.